2013
DOI: 10.1387/revpsicodidact.6776
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Success in Teamwork of Secondary Students // Predicción del éxito en el trabajo en equipo de estudiantes de Secundaria

Abstract: This study aimed to identify the factors that predict success in a teamwork task with secondary students. The following factors, which have been established by research as key elements in the resolution of teamwork task in a cooperative way, were treated as the independent variables: gender composition, group objectives, distribution of roles, interaction patterns, goal orientation, social atmosphere, reciprocal support, effective time focused on work and group self assessment. The study consisted of 87 triads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 33 publications
2
8
0
4
Order By: Relevance
“…The interdependence generated within the team is the essence of all teams [7,8], and it indicates the degree to which their members interact with each other. It also indicates how the team members depend on each other to achieve their goals, to get involved in the task [9], or to achieve rewards [10].…”
Section: Introductionmentioning
confidence: 99%
“…The interdependence generated within the team is the essence of all teams [7,8], and it indicates the degree to which their members interact with each other. It also indicates how the team members depend on each other to achieve their goals, to get involved in the task [9], or to achieve rewards [10].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, other contributions highlighted that in mixed-gender groups individuals' knowledge tends to diverge more than in single-gender groups, and these processes should be important elements for positive results in collaborative learning [30]. For some authors, having a majority of females in a group is one of the best predictors of successful group outcomes [31], whilst other researchers suggest that having a female-only and a balanced-gender group are two types of good grouping interventions for CSCL [32]. Little research focused on the effects of gender grouping on female and male participants' learning in VEs, and these studies showed controversial results [32].…”
Section: Effects Of Individual Characteristics: Personality Traits State Anxiety and Gender On Collaborative Learningmentioning
confidence: 99%
“…Literature in CSCL examines gender in terms of performance, attitude towards the course, learning outcomes and group success (Monereo, Castello, & Martinez-Fernandez, 2013;Zhan, Fong, Mei, & Liang, 2015). Gender and its relationship with communication, interaction styles, quality of discussion and collaboration is also reviewed (Asterhan, Schwarz, &Gil, 2012;Takeda & Homberg, 2014).…”
Section: Review Of Related Literature Gender In Mooc Groups and Othermentioning
confidence: 99%